China’s Maritime Strategy and Its Impact on the Security Perceptions of Southeast Asian States - Okwara, Emmanuel Chukwuma (Kashere Journal of Politics and International Relations, 2025)
The study explores China’s maritime strategy and its impact on the security perceptions of Southeast Asian states, drawing upon secondary data from government reports, policy papers, journal articles, and regional security analyses. Over the past two decades, China’s assertive actions in the South China Sea—such as island reclamation, increased naval patrols, and the construction of military installations—have significantly altered the strategic landscape of Southeast Asia. While Beijing frames these actions as part of its sovereign rights and maritime defense, neighboring countries perceive them as coercive, destabilizing, and indicative of expansionist ambitions. The study adopts a qualitative content analysis approach to examine how states like Vietnam, the Philippines, and Malaysia have responded to these developments through policy adjustments, defense cooperation, and diplomatic engagement. Findings reveal a deepening security dilemma in the region, with affected states strengthening bilateral ties with external powers such as the United States and Japan, while also expressing cautious commitment to multilateral conflict-resolution mechanisms through ASEAN. The research underscores how strategic narratives, historical grievances, and power asymmetries contribute to divergent threat perceptions and policy responses. It concludes that unless mitigated by genuine dialogue and confidence-building measures, China’s maritime posture will continue to generate mistrust and fuel regional insecurity.